Experimental investigation of scour induced by twin-propeller wash - Yew W.-T.; Hashim R.; Ng K.-C. (American Society of Civil Engineers (ASCE), 2023)
Propellers; Scour; Sediment transport; Clearance ratio; Densimetric Froude number; Experimental investigations; Highly-correlated; Noncohesive soil; Protection measures; Reference time; Scour depth; Ship propulsion; experimental study; Froude number; scour; seafloor; sediment transport; vessel